PROMOTING THE JUNIOR HIGH SCHOOL STUDENTS’ VOCABULARY KNOWLEDGE THROUGH SEMANTIC MAPPING STRATEGY IN WRITING SKILL - Katarina Alviani Mbaki; Ririn Pusparini (Journal of English Language Teaching and Literature (JELTL), 2023)
The study investigated how teacher encouraged junior high school student’s vocabulary knowledge by using semantic maps on writing skills and examined what vocabulary knowledge could be promoted by semantic mapping through students' report text writing. This study used a qualitative method, with the research participants being 35 students of SMPN 28 Surabaya consisting of 17 boys and 18 girls. The instruments used in this study were field notes and students’ report text writing. Field note was used to find out how the teacher implemented semantic mapping to encourage students' vocabulary knowledge in writing skill. At the same time, Student writing was used to answer how students' vocabulary knowledge is in the report text and what vocabulary knowledge was promoted by semantic mapping. The outcome of this study showed that the teacher implemented semantic mapping through several stages, such as introducing brainstorming, categorizing, personalizing, and writing. Furthermore, semantic mapping engaged students' attention to always focus on the learning process, assisted them to prepare ideas and information before writing a report text, explored and connected their vocabulary knowledge to the topic. In addition, based on the results of student report text analysis, which was done in groups, semantic mapping helped them to encourage vocabulary knowledge, classified vocabulary according to its categories and facilitated students to use vocabulary according to the context in the report text. Semantic mapping encouraged three students' vocabulary knowledge: word recognition, word grouping, and word context. By having good vocabulary knowledge, students could produce appropriate report text writing.